2017
DOI: 10.1111/mila.12148
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Mental Primer

Abstract: Drawing on the empirical premise that attention makes objects look more intense (bigger, faster, higher in contrast), Ned Block has argued for mental paint, a phenomenal residue that cannot be reduced to what is perceived or represented. If sound, Block's argument would undermine direct realism and representationism, two widely held views about the nature of conscious perception. We argue that Block's argument fails because the empirical premise it is based upon is false. Attending to an object alters its sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…The debate about whether our subjective perceptual experience is influenced by higher cognitive functions such as attention is a contentious issue in neuroscience, psychology and philosophy (Anton-Erxleben et al, 2010, 2011Beck & Schneider, 2016;Block, 2010;Carrasco et al, 2004;Firestone & Scholl, 2015;Fodor, 1984;Helmholtz, 1866;James, 1890;Ling & Carrasco, 2007;Prinzmetal et al, 1996;Pylyshyn, 1999;Raftopoulos, 2001;Schneider & Komlos, 2008;Schneider, 2011). Here, we show that the effects of spatial attention on visual appearance and on response bias can coexist and that the balance between these two types of modulation depends upon stimulus visibility.…”
Section: Discussion (623 Words)mentioning
confidence: 67%
See 2 more Smart Citations
“…The debate about whether our subjective perceptual experience is influenced by higher cognitive functions such as attention is a contentious issue in neuroscience, psychology and philosophy (Anton-Erxleben et al, 2010, 2011Beck & Schneider, 2016;Block, 2010;Carrasco et al, 2004;Firestone & Scholl, 2015;Fodor, 1984;Helmholtz, 1866;James, 1890;Ling & Carrasco, 2007;Prinzmetal et al, 1996;Pylyshyn, 1999;Raftopoulos, 2001;Schneider & Komlos, 2008;Schneider, 2011). Here, we show that the effects of spatial attention on visual appearance and on response bias can coexist and that the balance between these two types of modulation depends upon stimulus visibility.…”
Section: Discussion (623 Words)mentioning
confidence: 67%
“…Using a similar method, other studies have demonstrated that the effect of attention on appearance generalizes to other stimulus features including spatial frequency (Gobell & Carrasco, 2005), object shape and size (Anton-Erxleben, Henrich, & Treue, 2007;Fortenbaugh, Prinzmetal, & Robertson, 2011), and facial attractiveness (Störmer & Alvarez, 2016). However, in another set of studies, Schneider and collegues argue that these changes in appearance are instead related to response bias induced by the attention cues (Beck & Schneider, 2016;Schneider & Komlos, 2008;Schneider, 2006Schneider, , 2011. In support of this view, other studies have shown that attention can induce a response bias in a way that makes observers more likely to respond to a cued attended stimulus compared to an un-cued unattended stimulus (Luo & Maunsell, 2015;Müller & Findlay, 1987;Wyart, Nobre, & Summerfield, 2012).…”
Section: Introduction (556 Words)mentioning
confidence: 99%
See 1 more Smart Citation
“…34. See Beck and Schneider (2017) for dissent from this interpretation, and discussion of the results. 35.…”
Section: Bayesian Models Claim That New and Old Information Is Integrmentioning
confidence: 99%
“…It would only have that kind of effect post-perceptually, at the level of perception-based judgment. (See Beck and Schneider, forthcoming for philosophical discussion, replying to Block, 2010 .) If these moves (or others) were to pan out, they would vindicate Pylyshyn’s claim that attentional effects—or at least the relevant ones—are all external to early vision.…”
Section: Pylyshyn’s Argument and Its Criticsmentioning
confidence: 99%